Banking Preferences and Perceptions Among College Students: A Study on Influential Factors and Service Satisfaction - Shrestha, Rojina; Shrestha, Sushma (International Journal of Atharva, 2024)
This study investigates customer perceptions of their choice of bank among college students, focusing on factors influencing their banking decisions. Through a survey of 150 respondents, the study reveals that most students prefer commercial banks, valuing service quality and security. The majority have not utilized bank loans or relief measures during the COVID-19 pandemic. Dissatisfaction with service or limited options are common reasons for considering a bank switch. While respondents generally rate their banks positively, there are varied opinions on employee behavior, individual attention, and operating hours. The findings indicate that while overall perceptions are favorable, there is room for improvement in specific service aspects. This research provides insights into student banking preferences and highlights areas for banks to enhance their service offerings.